TECHNOLOGY OF VANADIUM EXTRACTION FROM VARIOUS RAW MATERIALS - Mаmаrаimоv Gаyrаt Fаrhоdоvich (Digital technologies in industry, 2025)
In recent years, due to the global growth in the production of structural, stainless and special steels, the level of vanadium consumption in the world has been steadily increasing. In addition to the metallurgical and chemical industries, vanadium and its compounds are widely used in nuclear power and battery production. In connection with the development of new technologies for the extraction of vanadium and other rare metals from ores and other types of raw materials containing rare metals, the introduction of rare metal extraction into practice is of particular importance in the metallurgical industry. Currently, scientific work is actively underway on the processing of man-made waste from the mining and metallurgical industry, accumulated over many years.